Candidate medical countermeasures targeting Ebola virus cell entry. (March 2017) - Liang, Janie; Jangra, Rohit K; Bollinger, Laura; Wada, Jiro; Radoshitzky, Sheli R; Chandran, Kartik; Jahrling, Peter B; Kuhn, Jens H; Jensen, Kenneth S
Medical countermeasures (MCMs) against virus infections ideally prevent the adsorption or entry of virions into target cells, thereby circumventing infection. Recent significant advances in elucidating the mechanism of Ebola virus (EBOV) host-cell penetration include the involvement of two-pore channels at the early stage of entry, and identification of cellular proteases for EBOV spike glycoprotein maturation and the intracellular EBOV receptor, Niemann–Pick type C1. This improved understanding of the initial steps of EBOV infection is now increasingly applied to rapid development of candidate MCMs, some of which have already entered the clinic. Candidate MCMs discussed include antibodies, small molecules and peptides that target various stages of the described EBOV cell-entry pathway. In this review, we summarize the currently known spectrum of EBOV cell-entry inhibitors, describe their mechanism of action and evaluate their potential for future development.